Unveiling the role of adenosine A2A receptors on neurogenesis induced by activation of cannabinoid receptors in rat SVZ and DG stem/progenitor cell cultures - Rodrigues, Rui Miguel Silva (2015)
Dissertação de Mestrado em Biologia Celular e Molecular, apresentada ao Departamento de Ciências da Vida da Faculdade de Ciências e Tecnologia da Universidade de Coimbra.